Alarming use of Psychoactive Drugs Amongst Medical Under and Post Graduate Students - Syed Muhammad Shahkar Ali, Aqeela Iqbal, Amanat Ali, Inayatullah Awan, Abid Usman, Samreen Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to assess the prevalence and factors associated with the use of psychoactive drugs amongst medical undergraduate and postgraduate students. Study Design: A cross-sectional study was conducted using a self-administered questionnaire to obtain information on the consumption patterns of psychoactive substances. Study Place and Duration: The study was carried out at Department of Psychiatry, Khyber Teaching Hospital Peshawar, Khyber Pakhtunkhwa, over a period of twelve months from January, 2022 to December, 2022. Methods: A total of 2,500 medical students, comprising 1,800 undergraduates and 700 postgraduates, were randomly selected from the participating institution. The questionnaire collected data on demographics, academic performance, substance use, and factors contributing to the consumption of psychoactive drugs. Data were analyzed using descriptive statistics, chi-square tests, and logistic regression models. Results: The overall prevalence of psychoactive drug use among the medical students was found to be 35.8%, with a higher rate among postgraduate students (42.1%) compared to undergraduates (32.6%). The most commonly used substances were stimulants, followed by opioids and sedatives. Factors significantly associated with psychoactive drug use included high levels of stress, academic pressure, and peer influence. Students who reported using psychoactive drugs had a higher incidence of poor academic performance and mental health issues. Gender differences were also observed, with male students showing a higher prevalence of substance use than female students. Conclusion: The study highlights the alarming prevalence of psychoactive drug use among medical undergraduate and postgraduate students, which can adversely impact their academic performance, mental health, and future professional lives. It is imperative for educational institutions and policymakers to implement targeted interventions to address the underlying factors contributing to substance use, such as stress management and peer support programs. Furthermore, fostering a culture of open dialogue and increasing awareness about the consequences of psychoactive drug use can help mitigate this growing public health concern. Keywords: psychoactive drugs, medical students, undergraduate, postgraduate, prevalence, substance use, academic performance, stress, mental health.